Potential of Alternative Organic Binders in Briquetting and Enhancing Residue Recycling in the Steel Industry - Elsayed Mousa; Hesham Ahmed; Daniel Söderström (Recycling, 2022)
Steel production generates various types of residues that cannot be directly recycled in the production process without pre-treatment and agglomeration. In the present study, recipes were designed to develop briquettes in a blast furnace (BF) with the partial replacement of cement with alternative commercial organic binders, including molasses–lime, bitumen, keracoal, carboxymethyl cellulose, and wood tar. The briquettes were produced using a technical-scale vibrating machine and the mechanical strength was evaluated using drop test and standard tumbler index results. The reduction behaviour was investigated by thermogravimetric analysis (TGA) coupled with QMS. A heat and mass balance model (MASMOD) was used to evaluate the potential of developed briquettes to reduce the energy consumption and CO2 emissions from the BF. Although cement was superior in developing mechanical strength, bitumen was the best among the other alternative organic binders and provided sufficient strength to the briquettes at 2.0% addition, which corresponded to 18.2% replacement of total cement. The briquettes containing bitumen possessed a higher reduction rate and lower activation energy compared to cement. The MASMOD calculation demonstrated that the developed briquettes have the potential to provide annual savings of 15,000–45,000 tons of lump coke, 4500–19,500 tons of CO2 emissions, and 5000–20,000 tons of limestone in Swedish BFs.